Effectiveness of giving tongkol fish and moringa oleifera to increase hemoglobin levels in anemic pregnant women - Yonni Siwi, Retno Palupi; Beverli, Beverli; Wulandari, Anggrawati (Institute of Computer Science (IOCS), 2024)
Anemia in pregnant women is a health problem associated with a high incidence of bleeding and can cause complications both in the mother and in the fetus. The purpose of this study was to determine the effectiveness of giving tongkol fish and Moringa Oleifera to increase hemoglobin levels in anemic pregnant women. This design research is quasy-experiments with purposive sampling technique obtained a sample of 30 respondents. The independent variable is the provision of tongkol and Moringa Oleifera, the dependent variable is the increase in hemoglobin levels, with independent T-test statistics. Average hemoglobin levels of respondents before receiving treatment tongkol are 10.3 gr/dL, after receiving treatment tongkol fish are 12 gr/dL, before receiving treatment Moringa Oleifera are 10.3 gr/dL, after receiving receiving treatment Moringa Oleifera are 1 gr/dL. The analysis results are p = 0.001 < 0.05, so H1 is accepted this means that giving tongkol fish and Moringa Oleifera is effective in increasing hemoglobin levels in anemic pregnant women. Providing additional food from local ingredients in the form of tongkol fish and Moringa Oleifera as an additional source of iron is one alternative solution to increase hemoglobin levels in pregnant women.